3D printable concrete: Mixture design and laboratory test methods - Thi Loan Pham; Xiao Jian Zhuang; Thi Hoai Thu Nguyen; Phan Anh Nguyen; Duy Thanh Trinh; Trong Quang Do (Vietnam Journal of Science, Technology and Engineering, 2023)
Experimental results of the mix design and fresh properties of a proposed concrete for 3D printing are presented in this paper. Layer-by-layer sample components were built by the designed concrete and extruded through a nozzle. The two most critical rheological properties of the designed mix are extrudability and buildability as they are both highly influenced by mix proportion and the presence of superplasticizers. Therefore, this study focused on mix proportion design approaches and laboratory test methods, which generally allowed access to the fresh concrete’s printable properties. Because they are efficient and convenient in construction, materials including cement, fly ash, natural sand, and superplasticizer were selected for mixing proportion analysis. Slump-flow tests, V-funnel tests, buildability tests, and extrudability tests were also employed to access the printability of the proposed mixture in this study. This first analysis on the mixture design approach and laboratory test methods to evaluate the printable properties of 3D-printable concrete can be considered a reference and orientation to further develop 3D printing technology in Vietnam.